2020
DOI: 10.3390/cancers12092659
|View full text |Cite
|
Sign up to set email alerts
|

NK-Cell-Mediated Targeting of Various Solid Tumors Using a B7-H3 Tri-Specific Killer Engager In Vitro and In Vivo

Abstract: We improved the bispecific antibody platform that primarily engages natural killer (NK) cells to kill cancer cells through antibody-dependent cellular cytotoxicity (ADCC) by adding IL-15 as a crosslinker that expands and self-sustains the effector NK cell population. The overall goal was to target B7-H3, an established marker predominantly expressed on cancer cells and minimally expressed on normal cells, and prove that it could target cancer cells in vitro and inhibit tumor growth in vivo. The tri-specific ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 53 publications
0
62
0
Order By: Relevance
“…Within the same study, in vivo studies found that TriKEs had superior antitumor activity and sustained NK cell survival for at least three weeks. The same effects were seen when ovarian, prostate and lung cancers were used, highlighting that TriKEs are effective against solid tumors [ 262 ]. Although TriKEs used in these studies contained IL-15, and IL-15 elicited severe toxicity (bowel ischemia, pneumonitis, papilledema, uveitis and grade 3 hypotension) and death in humans [ 256 ], IL-15-incorporting TriKEs showed no observable detrimental effects in mice [ 263 ].…”
Section: Nk Cells In the Context Of Immunotherapiesmentioning
confidence: 87%
“…Within the same study, in vivo studies found that TriKEs had superior antitumor activity and sustained NK cell survival for at least three weeks. The same effects were seen when ovarian, prostate and lung cancers were used, highlighting that TriKEs are effective against solid tumors [ 262 ]. Although TriKEs used in these studies contained IL-15, and IL-15 elicited severe toxicity (bowel ischemia, pneumonitis, papilledema, uveitis and grade 3 hypotension) and death in humans [ 256 ], IL-15-incorporting TriKEs showed no observable detrimental effects in mice [ 263 ].…”
Section: Nk Cells In the Context Of Immunotherapiesmentioning
confidence: 87%
“…Of note, GT Biopharma is also developing two TriKEs against solid tumors: GTB-4550 targeting PD-1, and GTB-5550 targeting B7H3 [ 174 ]. Additional TriKEs are in preclinical stage, such as 161,533 targeting CD33 [ 175 ], or a slightly different construct targeting B7-H3 and using an sdAb to bind CD16 [ 176 ]. Another related variant are trispecific “NK-cell engagers” (NKCE), which recruit NK cells by using scFv or Fab against TAA, NKp46, and CD16 [ 177 ].…”
Section: Trispecific and Other Multispecific Antibodiesmentioning
confidence: 99%
“…These antibodies show promise in vitro and in vivo , but most clinical research has been restricted to hematologic malignancies ( 115 ). To study the antibodies in mice, researchers have used xenogenic models such as NSG mice injected with human ovarian cancer cells and NK cells ( 116 ). Another novel NK cell stimulating antibody is a trifunctional NKCE that binds to NKp46 and CD16 on NK cells and a tumor antigen on target cells.…”
Section: Ilc Immunotherapeutics Studies In Murine Hostsmentioning
confidence: 99%